2016
DOI: 10.1007/s11240-016-0962-0
|View full text |Cite
|
Sign up to set email alerts
|

High throughput transformation of a Sorghum cDNA library for rice improvement

Abstract: The improvement of rice productivity is an important subject due to great population pressure. As plant functional genomics rapidly develops, increasing numbers of genes from different organisms are documented for rice improvement. Sorghum, a relative of rice, has many novel phenotypic characteristics such as strong stature, large panicle, drought tolerance, and a tolerance for low soil fertility, making this species an excellent gene resource for rice improvement. A Sorghum cDNA library was transformed into r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…So far, many examples have shown that the introgression of favorable exogenous genes in rice plays a vital role in improving the yield, quality, and resistance, which is an effective tool for the innovation of rice germplasm resources [ 20 , 21 , 22 , 23 ]. Among the distant hybrids of rice, crosses with sorghum have been more intensively and maturely studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, many examples have shown that the introgression of favorable exogenous genes in rice plays a vital role in improving the yield, quality, and resistance, which is an effective tool for the innovation of rice germplasm resources [ 20 , 21 , 22 , 23 ]. Among the distant hybrids of rice, crosses with sorghum have been more intensively and maturely studied.…”
Section: Discussionmentioning
confidence: 99%
“…SbSGL encodes a DUF1645 superfamily protein in sorghum, and its transfer to rice significantly increased the size and number of glume cells and post-fertilization filling rate, which in turn led to a highly significant increase in grain length and 1000-grain weight [ 20 ]. Qin et al introgressed sorghum cDNA into the rice and more than 92% of the 965 transgenic lines obtained different phenotypic changes, including longer leaves and increased effective spike number [ 21 ]. In this study, R21 was a rice variant line obtained by introgressing sorghum DNA into the rice restorer line Jin Hui 1, and the content proline, SOD and POD activities, and MDA of R21 were significantly increased after being subjected to high temperature and drought stress, indicating that R21 has excellent heat tolerance and drought tolerance [ 15 ].…”
Section: Discussionmentioning
confidence: 99%